Temperature field of a thermoelectric system for extracting foreign objects when introducing into the human body - O. V. Evdulov; A. M. Nasrulaev (Вестник Дагестанского государственного технического университета: Технические науки, 2021)
Objective. The objective of the article is to create a design model of a thermoelectric system for extracting foreign objects from the human body by freezing when introduced into the cavity, as well as to study the internal thermophysical processes.Methods. A design model of a thermoelectric system for extracting foreign objects from the human body by freezing the thermoelectric system introduced into the cavity is developed, based on solving the problem of thermal conductivity, taking into account the thermophysical characteristics of a biological object, foreign object, and a thermoelectric module.Results. As a result of the numerical experiment, the authors obtained graphs of temperature changes at various points of the thermoelectric system when introduced into the human body to extract a foreign object, depending on the power of the thermoelectric system, the parameters of the module materials, and external conditions. It is determined that the device can use a standard thermoelectric module with a cooling capacity from 4500 W/m2 to 7000 W/m2 with a duration of 6-7 minutes for entering the system mode.Conclusion. It is established that the selection of thermoelectric module parameters must be guided by the limitations of the device operation, as well as medical norms and standards to avoid the process of cold injury of adjacent tissues, which is fully provided in the proposed design. A method for improving the efficiency of the system is proposed, according to which the thermoelectric system is pre-cooled using an external cold source, and forced modes of thermoelectric module operation are used.